Survey Attention and Self-Reported Political Behavior. Issue 4 (2nd February 2023) - Alvarez, R Michael; Li, Yimeng
Abstract: Survey research methodology is evolving rapidly, as new technologies provide new opportunities. One of the areas of innovation regards the development of online interview best practices and the advancement of methods that allow researchers to measure the attention that respondents are devoting to the survey task. Reliable measurement of respondent attention can yield important information about the quality of the survey response. In this article, we take advantage of an innovative survey we conducted in 2018, in which we directly connect survey responses to administrative data, allowing us to assess the association between survey attention and response quality. We show that attentive survey respondents are more likely to provide accurate survey responses regarding a number of behaviors and attributes that we can validate with our administrative data. We discuss the best strategy to deal with inattentive respondents in surveys in light of our results.